Города и степи Крыма в XIII-XIV вв. по археологическим свидетельствам - Айбабин, А.И. (Материалы по археологии, истории и этнографии Таврии, 2003)
Nomadic Comans or Kipchaks, who are called the Polovcians in Russian chronicles, conquered the steppes of the Northern Black Sea littoral, which had been in the possessions of the Pechenegs in the middle of the 11th century. On the Crimean plain the Comas - Polovcians made their burials in mounds of earlier barrows. In those graves there was a horse skeleton or a staffed horse lying near a human skeleton, the cranium of which was oriented to the east (PI. 1,2,7, 8,25). The author dates these burials back to the end of the 11th -13th centuries. According to the written and archaeological sources, in the period when the Codex Cumanicus was compiled, i.e. in the 13th century - the 1330s, Krym-Solkhat, Soldaia, Vosporo (Kerch) and Kaffa were large trading cities, in contrast to depopulated Cherson. All the aforementioned cities had, among others. Coman population. There were Catholic monasteries in each of the four cities. One of these cloisters could collect linguistic material for the Codex Cumanicus.